Mental health services and community care : a critical history - Cummins, Ian (Policy Press, 2020)
This inter-disciplinary study considers the past, present and future of mental health services and community care. From the origins of provision as we know it in the 1960s, it sets out the political, economic and bureaucratic factors behind recent crises and considers what the founding principles of community care tell us about the way forward.